2001
DOI: 10.1097/00126334-200106010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ritonavir/Saquinavir on Stereoselective Pharmacokinetics of Methadone: Results of AIDS Clinical Trials Group (ACTG) 401

Abstract: Our data indicate that ritonavir/saquinavir administration is associated with induction of metabolism of methadone but this is greater for the inactive S-methadone. However, approximately 37% of the decrease in the total R-methadone exposure can be explained by protein binding displacement. Ritonavir/saquinavir can be used in HIV-infected people taking methadone without routine dose adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 22 publications
1
30
2
2
Order By: Relevance
“…One explanation for the difference in findings for this study and that by Clark et al [11] is that the mean trough methadone level (‫ע‬SD) after L/R administration for the participants in the current study who developed opiate-withdrawal symptoms was mg/L, well less than the minimum therapeutic 143.5 ‫ע‬ 16.7 trough methadone concentration of 200 mg/L. It has been suggested that the clinical consequences of the decrease in methadone levels seen in conjunction with protease inhibitor use may be mitigated by changes in protein binding and disparate effects on the 2 enantiomers of methadone [18]. However, in this instance, the significant increase in withdrawal symptoms was consistent with the observed reductions in the AUC and trough concentrations of methadone after L/R therapy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…One explanation for the difference in findings for this study and that by Clark et al [11] is that the mean trough methadone level (‫ע‬SD) after L/R administration for the participants in the current study who developed opiate-withdrawal symptoms was mg/L, well less than the minimum therapeutic 143.5 ‫ע‬ 16.7 trough methadone concentration of 200 mg/L. It has been suggested that the clinical consequences of the decrease in methadone levels seen in conjunction with protease inhibitor use may be mitigated by changes in protein binding and disparate effects on the 2 enantiomers of methadone [18]. However, in this instance, the significant increase in withdrawal symptoms was consistent with the observed reductions in the AUC and trough concentrations of methadone after L/R therapy.…”
Section: Discussionmentioning
confidence: 62%
“…Effective methadone maintenance treatment in persons with HIV disease requires that health care providers be aware of important drug interactions between antiretroviral medications and opioids. However, reports of reduced methadone exposure do not necessarily correlate with the need for increased doses of methadone [2,18,21]. The administration of antiretrovirals shown to induce methadone metabolism will require careful clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…These recent investigations identified the prominent role of CYP2B6 in methadone metabolism in vitro , and the present observations may be consistent with a role for CYP2B6 in vivo . Recombinant CYP2B6 catalyzed methadone N-demethylation as effectively as CYP3A4, and moreover, unlike CYP3A4, metabolism by CYP2B6 was stereoselective (Gerber et al, 2004; Gerber et al, 2001; Kharasch et al, 2004a; Totah et al, 2007a; Totah et al, 2007b). In human liver microsomes, greater stereoselective metabolism (S>R) occurred in livers expressing high levels of CYP2B6 compared to CYP3A4, inhibition of CYPB6 caused the greatest reduction in methadone metabolism, and only CYP2B6 inhibition was stereoselective (Totah et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…Second, drug treatment has been shown not only to reduce illicit drug use but also to improve health behaviors and HIV clinical outcomes (Palepu, Horton, Tibbetts, Meli, & Samet, 2004). Third, allowing a single medical provider to monitor both prescription and illicit drug use may reduce the occurrence of adverse drug–drug interactions, such as the known adverse effects of coadministration of methadone and many antiretroviral medications (Altice, Friedland, & Cooney, 1999; Bart et al, 2001; Beauverie, Taburet, Dessalles, Furlan, & Touzeau, 1998; Clarke, Mulcahy et al, 2002; Clarke et al, 2001a, 2001b; Gerber et al, 2001; McCance-Katz, Farber, Selwyn, & O’Connor, 2000; McCance-Katz, Rainey, Friedland, & Jatlow, 2003; Shelton et al, 2004; Stevens, Rapaport, Maroldo-Connelly, Patterson, & Bertz, 2003). Finally, integration of care is likely to decrease duplication of services and may therefore be more efficient and less costly.…”
Section: Review Of Key Strategies To Improve Access Utilization Andmentioning
confidence: 99%